2006
DOI: 10.1139/x06-052
|View full text |Cite
|
Sign up to set email alerts
|

Welfare effects of forestry best management practices in the United States

Abstract: State forestry best management practice (BMP) programs have been widely developed and implemented to prevent nonpoint source water pollution in the past three decades. The unanswered question is how forestry BMPs have affected the welfare positions of consumers, mills, loggers, and forest landowners. A Muth-type equilibrium displacement model was constructed to examine welfare changes of these stakeholders. The model considered a two-stage vertical production system with variable proportion production technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Logging contractors in West Virginia paid an average of US$1,426 per employee for formal BMP training (Egan et al 1996). Loggers directly incur most of the BMP costs in both the lumber and paper sectors of the forest products industry (Sun 2006), but costs are typically passed to the land or timber owner through lower stumpage prices (Cubbage 2004). Montgomery et al (2005) found that BMP implementation and compliance in Arkansas led to a 3.5% decrease in annual tonnage produced from 1998 to 2005, reducing gross profits for all parties involved.…”
mentioning
confidence: 99%
“…Logging contractors in West Virginia paid an average of US$1,426 per employee for formal BMP training (Egan et al 1996). Loggers directly incur most of the BMP costs in both the lumber and paper sectors of the forest products industry (Sun 2006), but costs are typically passed to the land or timber owner through lower stumpage prices (Cubbage 2004). Montgomery et al (2005) found that BMP implementation and compliance in Arkansas led to a 3.5% decrease in annual tonnage produced from 1998 to 2005, reducing gross profits for all parties involved.…”
mentioning
confidence: 99%
“…Second, this measurement is often obtained using sample means of an outdated econometric model that does not include the structural change that has occurred in recent years (Brown and Zhang 2005). These misspecifications can have significant effects, especially in the case where the model is investigating potential long run welfare changes associated with a given shock (Sun 2006). If the demand curve is assumed to be highly inelastic (as in the case of most of our SR estimates), then price changes will affect total welfare differently depending on the elasticity of the supply curve (which we found here to be price inelastic).…”
Section: Discussionmentioning
confidence: 99%
“…Most research in timber markets has focused on estimating econometric models of regional stumpage markets (Robinson 1974;Adams and Haynes 1980;Newman 1987). Other studies have considered the implications of specific policies (Brown and Zhang 2005;Wear and Murray 2004;and Sun 2006). For the most part, timber market studies have found stumpage demand to be price inelastic (table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jungtinių Tautų Gausu darbų, skirtų atskirų miškų ir visuomenės gerovės aspektų sąsajoms analizuoti: miškų įtaka ekonominei gerovei (Kant et al, 1996), gero miškų tvarkymo gerovės efektai (Sun, 2006), miškų ekosistemų paslaugų įtaka žmonių gerovei (Louman et al, 2009), klimato kaitos ir urbanizacijos sąsajos su miškais, žmonių sveikata ir gerovė (Hägerhäll et Pradėtos analizuoti miškų ūkio ir Darbotvarkės 2030 tikslų bei uždavinių sąsajos. Tampriausias ryšys nustatomas su 15 tikslu "Saugoti, atkurti ir skatinti darnų sausumos ekosistemų naudojimą, darniai valdyti miškus, kovoti su dykumėjimu, sustabdyti žemės būklės blogėjimą ir pakeisti šį procesą priešinga kryptimi bei sustabdyti biologinės įvairovės praradimą."…”
Section: įVadasunclassified